Disruption of erythroid nuclear opening and histone release in myelodysplastic syndromes - Baobing Zhao; Hui Liu; Yang Mei; Yijie Liu; Xu Han; Jing Yang; Amittha Wickrema; Peng Ji (Cancer Medicine)
Abstract Mammalian terminal erythropoiesis involves several characteristic phenomena including chromatin condensation and enucleation. One of the newly identified features of terminal erythropoiesis in mouse is a dynamic nuclear opening and histone release process, which is required for chromatin condensation. However, it is unclear whether the same feature is present in human. Here, we use an in vitro human CD34‐positive hematopoietic stem and progenitor cell culture system and reveal that nuclear openings and histone release are also identified during human terminal erythropoiesis. In contrast to mouse in which each erythroblast contains a single opening, multiple nuclear openings are present in human erythroblast, particularly during the late‐stage differentiation. The nuclear opening and histone release process is mediated by caspase‐3. Inhibition of caspase‐3 blocks nuclear opening, histone release, chromatin condensation, and terminal differentiation. We confirm the finding of histone cytosolic release in paraffin‐embedded human bone marrow in vivo. Importantly, we find that patients with myelodysplastic syndrome (MDS) exhibit significant defects in histone release in the dysplastic erythroblasts. Our results reveal developmentally conserved nuclear envelop and histone dynamic changes in human terminal erythropoiesis and indicate that disruption of the histone release process plays a critical role in the pathogenesis of dyserythropoiesis in MDS.